THE EFFECT OF GIVING BENGKOANG JUICE (PACHYRRHIZUS EROSUS) ON BLOOD CHOLESTEROL LEVELS AND COMFORT COMPLAINTS TO MENOPAUSE WOMEN IN BENGKULU CITY - Kurnia Dewiani (AKADEMI KEBIDANAN DHARMA HUSADA KEDIRI, 2020)
Most of the women have been experienced with menopausal syndrome 70-80 %. Estrogen and progesterone hormones activity decrease which the result of the cessation of menstruation followed by various physical and psychological changes. Blood cholesterol levels and complaints of discomfort are the effects of pre and menopause. Reducing the effect of menopause could be done with non-pharmacologically by utilizing natural materials that are easily available, cheap and minimal negative side effects, namely by consuming Bengkoang juice regularly for 21 days. This research aims to recognize the effect of giving Bengkoang juice by cholesterol levels and complaints of discomfort during menopause This research was a quasi-experimental pre-posttest with control group design. 30 pre and menopausal women participated in their resident of Tanah Patah Village, Bengkulu City with a purposive sampling technique was divided into two groups by simple random sampling. Each group was consisting of 15 women for treatment (Bengkoang juice) and control (soy milk). Assessment of cholesterol levels through an examination used a stick of cholesterol (easy touch), complaints used the questionnaire complaints, and respondents' compliance used the observation sheet. Statistical testing was applied paired T-Test analysis to see differences in cholesterol levels and complaints of discomfort between the two study groups with the significance of the test results based on p <0.05. The results present a decrease in cholesterol levels and complaints in both groups with a p-value <0.05. Furthermore, in terms of decreased levels of cholesterol (33%) and complaints (45%) were higher than the control group namely cholesterol levels (11%) and complaints ( 21%). This research concluded that the effect of Bengkoang juice on cholesterol levels and complaints of discomfort during menopause is confirmed.